2018
DOI: 10.1103/physrevapplied.10.024008
|View full text |Cite
|
Sign up to set email alerts
|

High-Field Magnetoresistance of Organic Semiconductors

Abstract: The magneto-electronic field effects in organic semiconductors at high magnetic fields are described by field-dependent mixing between singlet and triplet states of weakly bound charge carrier pairs due to small differences in their Landé g-factors that arise from the weak spin-orbit coupling in the material. In this work, we corroborate theoretical models for the high-field magnetoresistance of organic semiconductors, in particular of diodes made of the conducting polymer poly(3,4ethylenedioxythiophene):poly(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…Following the MEL studies at low temperature, we consider that the "Δg-mechanism" of spin-1/2 polaron pairs dominates the MEL response at cryogenic temperatures, as concluded in previous studies. [32,33,38] This mechanism should not be strongly isotope dependent though, in contrast to our observations shown in Figure 3c,d. The FWHM of the MEL(B) is generally not determined by the HFI when the Δg-mechanism governs the MEL response.…”
contrasting
confidence: 87%
“…Following the MEL studies at low temperature, we consider that the "Δg-mechanism" of spin-1/2 polaron pairs dominates the MEL response at cryogenic temperatures, as concluded in previous studies. [32,33,38] This mechanism should not be strongly isotope dependent though, in contrast to our observations shown in Figure 3c,d. The FWHM of the MEL(B) is generally not determined by the HFI when the Δg-mechanism governs the MEL response.…”
contrasting
confidence: 87%
“…To our knowledge, the experimental data presented above reflects the most comprehensive study of PEDOT:PSS magnetoresistance. It is consistent with previously reported behavior of magnetoresistance of PEDOT:PSS thin-film diodes, 14,23 and it reveals the full complexity of the PEDOT:PSS magnetoresistance due to its nontrivial dependence on the device operating point. Although it has been previously concluded that intermediate and ultrasmall magnetic field effects have to originate from different microscopic effects, given the strong differences in the evolution of the magnitude with magnetic field, the clear correlation of the FWHM of the intermediate magnetic field effect ΔB and the minimum of magnetoresistance attributed to the ultrasmall magnetic field effect B m put the interpretation of magnetoresistance data based on these phenomenological characteristics in question.…”
Section: Resultssupporting
confidence: 92%
“…The MC and MEL curves of organic materials have been shown to be well reproduced empirically by the non-Lorentzian function {H/(|H| + H 0 )} 2 (H 0 is the quarter-saturation field) 2,41 typically in the magnetic field region much lower than a few thousand gauss, over which the contribution from Δg-dependent MC could be dominant (Δg is the difference of the g-factor between the hole and electron carriers). 42 Actually, the obtained MC and MEL curves were found to match the function using the following parameters: H 0 values for MC are 20G (3.5 V) and 18G (4 V) and H 0 values for MEL are 30G (3.5 V) and 35G (4 V), as shown in Figs. 3(a) and 3(b).…”
Section: B Magnetic Field Effectsmentioning
confidence: 78%
“…We note here that, in the low magnetic field region typically below 50G, MC could include a low field effect indicated by the function of H 2 /(H 2 + H 0 0 2 ) (H 0 0 is a constant). 42,43 This effect is typically observed with the opposite sign to the contribution from the non-Lorentzian function. Yet, the MC in Fig.…”
Section: B Magnetic Field Effectsmentioning
confidence: 99%
See 1 more Smart Citation